Keadilan Sosial dalam Pendidikan Perspektif Al-Qur’an - Mahtum, Rohiki; Heryandi, M. Tubi (Fakultas Agama Islam, 2018)
Justice is a very important pillar in everything, especially education. With justice, various problems will be easily overcome. With justice all people get rights and obligations according to their capacity. In Indonesia sometimes there are several aspects that cause inequality in education. These aspects are partly discussed in this article namely, disability, prisoners, economics, and gender. The four aspects are often the reasons for the absence of justice in education in Indonesia.Indonesia as a Muslim majority community requires them to hold fast to the core teachings in Islam, which are following the Koran, Hadith, Ijma and Qiyas. In this article the author explains about the view of the Koran against these four aspects by being adapted from various verses that point to these four aspects.As a result the four aspects are not a reason for inequality in education and even become a motivator to pay more attention to them based on references from sources of Islamic teachings.